2021
DOI: 10.1039/d1ta02067f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Pt–Co nanoparticle motifs for enhancing the HOR performance in alkaline media

Abstract: For a future sustainable hydrogen economy, electrocatalysis of hydrogen oxidation/evolution reactions (HOR/HER) needs to be better understood. In order to describe the strong alteration of HOR/HER rates on platinum group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…According to well-established volcano plots of exchange current and calculated hydrogen binding energy (HBE, ΔG 0 H* ), good HOR catalysts like Pt show the optimal ΔG 0 H* value close to zero, [4,9] but stronger adsorption of H* on Pt sites takes place as pH increases from 1 to 14. [10,11] This issue can be solved by alloying Pt with secondary metal, such as Ru, [12][13][14][15] Pd, [3] Ni or its oxides, [16][17][18] Co, [19,20] and Cu, [21] to optimize the electronic density around Pt sites or oxophilic character. In this view, Markovic et al reported that the addition of Ru element into Pt catalyst rose the mass activity by about sixfold when compared to catalysts without modification.…”
Section: Introductionmentioning
confidence: 99%
“…According to well-established volcano plots of exchange current and calculated hydrogen binding energy (HBE, ΔG 0 H* ), good HOR catalysts like Pt show the optimal ΔG 0 H* value close to zero, [4,9] but stronger adsorption of H* on Pt sites takes place as pH increases from 1 to 14. [10,11] This issue can be solved by alloying Pt with secondary metal, such as Ru, [12][13][14][15] Pd, [3] Ni or its oxides, [16][17][18] Co, [19,20] and Cu, [21] to optimize the electronic density around Pt sites or oxophilic character. In this view, Markovic et al reported that the addition of Ru element into Pt catalyst rose the mass activity by about sixfold when compared to catalysts without modification.…”
Section: Introductionmentioning
confidence: 99%
“…We want to emphasize that the dealloying protocol has a huge impact on the resulting ECSA values for these precursor catalyst materials. 69 3.2. Chemical State of Both Metals in Dealloyed Pt x Co 1−x Core−Shell Nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen oxidation reaction (HOR) is the key to meet the requirements of renewable and clean energy conversion and energy storage in the hydrogen economy soon. [ 119 ] For domestic fuel cells, the fuel gas rich in H 2 is obtained by reforming. Trace CO in the reforming product poisons the HOR on platinum and blocks the active site.…”
Section: Electrocatalytic Applications Of Pt–co Catalystsmentioning
confidence: 99%
“…Lastly, it was also found that the particle size did not affect the effect of polycrystalline and nanosized Pt on the HOR activity in the alkaline medium. [ 119 ]…”
Section: Electrocatalytic Applications Of Pt–co Catalystsmentioning
confidence: 99%